Diskursus Media Online Tentang Problematika Jember Fashion Carnaval (JFC) di Kabupaten Jember - Bunga Surawijaya Ningsih (JURNAL PARADIGMA MADANI, 2022)
This research departs from the phenomenon of media in constructing reality. The reality displayed by the media is judged as the real truth by the audience, but the reality that is displayed by the media is not a single truth. As the reality of the 18th JFC controversy in 2019 becomes an interesting topic to discuss with Halliday discourse analysis model. Thus, the purpose of this study is to describe the online media discourse about the JFC problems in Jember district. This study uses a descriptive qualitative approach. The results of this study indicate that: 1) the mass media participate in the discourse of Muslim communication battles against reality through the construction of news in the mass media, especially online media; 2) The mass media, both electronic media and online media, talk about Cinta Laura Kiehl as one of the ambassadors whose appearance does not deserve to be displayed in the JFC event in media construction; and 3) the online media Bangsaonline.com and Potretjember.com talk about Cinta Laura Kiehl as an ambassador for the JFC event, which can damage the image of Jember as a city of students. Keywords: Discourse, Online Media, Problem JFC